Understanding User Acceptance towards Case Management System: A UTAUT Analysis - Tambunan, Ester Marta; Sensuse, Dana Indra; Sofian Lusa (The Indonesian Journal of Computer Science, 2024)
To improve the quality of case handling administration, the Indonesian National Police (Polri) has implemented a technology-based platform, a Case Management System (CMS). This study employs the UTAUT model to examine the factors influencing the interest of Polri investigators in using the CMS. Data were collected through an online survey distributed to all investigators within the Polri. Multivariate analysis using PLS-SEM was conducted to identify and predict the factors significantly influencing user acceptance. The results indicate that government policies and regulations, performance expectancy, and social influence significantly influence behavioral intentions towards the system, whereas effort expectancy does not. Behavioral intentions and facilitating conditions significantly influence system usage behavior. In conclusion, the UTAUT model demonstrates valid and reliable measurements, as well as a good goodness of fit in predicting investigators’ interest or intention to use the CMS system, which can be utilized for the development of information systems in government agencies.